Robust fault detection and estimation observer design for switched systems. (November 2019) - Li, Jian; Pan, Kunpeng; Zhang, Dezhen; Su, Qingyu
Abstract: The main purpose of this paper is to study the problem of fault detection and estimation for switched systems based on DC–DC converters. Firstly, we transform DC–DC converters into switched systems. Secondly, to achieve the purpose of the fault detection and estimation, we design a sliding mode observer(SMO) to produce residual signal. By comparing the set threshold and the residual produced by SMO, we can detect whether a fault has occurred. Meanwhile, fault estimation is realized through the method of fault reconstruction. Finally, in order to show the feasibility of this sensor fault detection and estimation, the simulation of three sensor faults which include open-circuit, gain deviation and noise abnormity is given in this paper.